Ověření znalostí studentů v oblasti BOZP - Veronika Lounová; Veronika Lounová (České vysoké učení technické v Praze, 2021)
Bakalářská práce se zabývá hodnocením a porovnáním znalostí studentů různých typů středních škol v oblasti bezpečnosti a ochrany zdraví (BOZ) a požární ochrany (PO). Práce je dělená na teoretickou a praktickou část. V první kapitole teoretické části je uveden pře-hled právních předpisů upravující BOZ žáků ve školách, způsoby zajištění BOZ žáků a specifika školních úrazů. Druhá kapitola teoretické části je věnována požární ochraně ve školách, kdy je opět uveden přehled právních předpisů upravující PO ve školách a dále jsou představeny programy HZS ČR pro školy. Praktická část se věnuje ověření a porovnání znalostí studentů středních škol formou dotazníkového šetření. Stanovena je jedna hlavní a čtyři vedlejší hypotézy, které jsou v závěru potvrzeny nebo vyvráceny. Dotazníky byly rozeslány do různých typů středních škol, aby bylo možné porovnat znalosti mezi studenty gymnázií, středního vzdělání s maturitou a středního vzdělání s výučním listem. Ukázalo se, že mezi žáky různých typů středních škol nejsou rozdíly ve znalostech v oblasti BOZ a PO. Žáci napříč školami jsou poučeni o zásadách bezpečného chování a požární ochrany a znají zásady bezpečného chování ve školách. Mezery mají žáci ve znalostech zásad poskytování první pomoci, která není na školách dostatečně vyučována. Nebyly na-lezeny rozdíly mezi znalostmi žáků v oblasti BOZ a v oblasti PO. Způsob poučení o bezpečnosti ve školách slovní formou považují žáci za nezáživný a preferovali by poučení interaktivní formou, tedy promítnutím prezentace či filmu. Na základě výsledků empirického šetření je školám doporučeno provádět poučení o bezpečnosti záživnější formou. Učitelé by měli s žáky procházet při poučení o bezpečnosti školu a upozornit na místa, kde je zvýšena hrozba nebezpečí a poučit žáky o místech, kde se nachází hasicí přístroje a lékárničky. Žáci by měli být lépe poučení o vhodnosti použití hasicích přístrojů pro hašení různých druhů požáru. Ukázalo se, že žáci nemají dostatečné znalosti v oblasti poskytování první pomoci, proto by výuka první pomoci měla být více zařazena do osnov učiva. Práce pro-zkoumala, vyhodnotila a porovnala znalosti studentů středních škol v oblasti BOZ a PO a stanovila doporučení pro zlepšení znalostí žáků.

This bachelor thesis deals with the evaluation and comparison of knowledge of students of different types of secondary schools in the field of health and safety and fire protection. The bachelor thesis is divided into theoretical and practical part. The first chapter of the theoretical part provides an overview of legal regulations governing the health and safety of students at schools, ways to ensure the health and safety of students and the specifics of school accidents. The second chapter of the theoretical part deals with the fire protection at schools, which provides an overview of legal regulations governing fire protection at schools and the programs of the Fire and Rescue Service of the Czech Republic for schools. The practical part is devoted to verification and comparison of the knowledge of high school students in the form of a questionnaire. One main and four secondary hypotheses are introduced, that are confirmed or refuted in the conclusion. Questionnaires were sent to different types of secondary schools in order to compare knowledge between grammar school students and high school students. It turned out that there are no differences in knowledge in the field of health and safety among students of different types of secondary schools. Students across schools are taught the principles of safe behaviour and fire protection and know the principles of safe behaviour in schools. Students have gaps in their knowledge of the principles of providing first aid, which is not sufficiently taught at schools. No differences were found between the students’ knowledge in the field of health and safety and in the field of fire protection. Students consider the way of teaching about health and safety in schools verbally to be tedious and would prefer instruction in an interactive form, i.e. by projecting a presentation or a film. Based on the results of the research, schools are encouraged to implement safety instruction in a more interesting form. Teachers should go through the school with the students when instructing about safety and point out places where the threat of danger is increased and instruct students about the places where fire extinguishers and first aid kits are located. Students should be better instructed in the suitability of fire extinguishers for extinguishing different types of fires. It turned out that students do not have sufficient knowledge in the field of first aid, so the teaching of first aid should be more included in the study plan. The work examined, evaluated and compared the knowledge of high school students in the field of occupational safety and health and set recommendations for improving the knowledge of students.
Verification of Students' Knowledge of Health and Safety Regulations
Keywords: Bezpečnost a ochrana zdraví; BOZP; požární ochrana; PO; bezpečnost; zdraví; požár; škola; Health and safety; fire protection; safety; health; fire; school